PENGARUH PEMBINAAN ASRAMA TERHADAP PEMBENTUKAN KARAKTER MAHASISWA STT KRISTUS ALFA OMEGA TAHUN AJARAN 2018/2019 - Tandiongan, Fianus (Shift Key : Jurnal Teologi dan Pelayanan, 2018)
When humans pray it will have an impact on changes in their character, including changes in behavior, and reflecting the character of Christ in his life. When humans have a change in character that means he has love in his life that affects himself and others. Evidence of love that is possessed by humans through the life of prayer for changes in their character, that is, with humans, likes to help their fellow students. Have mercy on people who need help when other people have trouble because when humans have had a change of character it will be able to be seen once from their daily lives and humans always have positive thoughts because humans know that God is the source of inner strength his life. This study uses a quantitative method of correlational description of data collection techniques in the form of questionnaires, data analysis techniques using correlational quantitative methods. The results of this study, namely; The first hypothesis "It is suspected that the level of boarding life in the student dormitory of the STT Kristus Alfa Omega Semarang is in the medium category or" 70% "is rejected because the value obtained is 76.126%. The second hypothesis "It is assumed that the level of character formation of the STT Kristus Alfa Omega Semarang Semarang is in the moderate category or â‰¤ 75%" because the value obtained is 81.65%. And the third hypothesis "It is assumed that there is a positive influence and in the medium category between boarding life on the formation of the character of the STT Kristus Alfa Omega Semarang" accepted because the coefficient value obtained is 0.441 which is positive and in the medium category.